(untitled) (Global Journal of Management and Business Research, 2013)
Building social capital (SC) is increasingly recognized as essential for organizational and social growth. However, there is a scant amount of literature on how leaders are expected to develop SC as an individual and organizational competence. While this article develops new frameworks for both SC and global leadership (GL), it offers practical suggestions to practitioners in human resource development and management on how they can set up strategies for developing both GL and SC.